(untitled) (Journal of Information Technologies in Education (ITE), 2014)
The article provides a technique of training activities for future masters of using information technology as an example of discipline "Information technologies in science and education."Defined and characterized every stage of the educational process masters in the application of learning technologies and the use of certain technologies. The results verify the effectiveness of this technique and the analysis of questionnaires experimental groups.